2008
DOI: 10.2174/1874372200802010022
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Necrobiosis Lipoidica with 595 nm Pulsed Dye Laser - A Case Report

Abstract: Abstract:Introduction: Necrobiosis Lipoidica (NL) had no adequate treatment. Some case has been treated by different vascular lasers. Third generation pulsed dye lasers with a wavelength of 595 nm has been attempted. Their selectively destroys shallower ectatic blood vessels. Material and Methods:We used a 595 nm, Dermobeam 2000 ® laser (manufactured by Deka© MELA Calenzano, Italy), with a dynamic skin cooling system (Spray). The parameters were 7 mm spot, 6 J/cm 2 , 0.5 Hz, and 0.5 msec.Case Report: A young C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…In the 1980s–1990s, there were reports of argon, Nd:YAG and potassium titanyl phosphate laser, but recent reports are primarily about treatment using dye laser. Morelli et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1980s–1990s, there were reports of argon, Nd:YAG and potassium titanyl phosphate laser, but recent reports are primarily about treatment using dye laser. Morelli et al.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed no difference between complete and nearly complete clearance with early laser treatment compared to observation alone at 1 year of age. 72 Other studies have demonstrated good results with either the 585 nm PDL or 595 nm PDL on superficial IH, but not deep IH. 73,74 Severe ulceration and scarring have been reported, particularly when treating segmental hemangiomas during the proliferative phase.…”
Section: Treatmentmentioning
confidence: 96%
“…The choice of laser depends on location, depth and size of the lesion. Flash lamp pumped pulsed dye laser with a wavelength of 585 or 595mm is the only laser that photo coagulates the target vessels leaving the overlying skin intact thereby making it useful for superficial Hemangiomas or those at involution stage, however it is of little use in deep seated Hemangiomas because of limited penetration depth 29 . Neodymium Yttrium aluminum garnet laser (Nd:YAG) having wavelength of 1064nm and penetration depth of 5mm is the choice for larger or 2cm deep seated Hemangiomas.…”
Section: Vimanagementmentioning
confidence: 99%